Impact of Gender Based Discrimination on Employee Performance in Case of Nepalese Commercial Banks - Nepal, Jenita; Lertjanyakit, Hatairat (Nepalese Journal of Management Science and Research, 2019)
This study deals with the concept of gender discrimination at workplace and how such discrimination can influence the employee performance in commercial banking sector of Nepal. The independent variables are the dimensions of gender discrimination specifically promotion, recruitment and selection, compensation and benefits. Similarly, the dependent variable taken is the employee performance. Quantitative tools are applied to analyze the data such as correlation and multiple regressions. The study reveals that gender discrimination in promotion and recruitment policies contributes more for the variation in dependent variable employee performance. The gender discrimination in compensation and benefits has least and insignificant effect on employee performance. Therefore, this empirical study provides guidelines for managers and human research practitioners in deducing discriminatory practices from the organization, in order to ensure equality and fairness for increasing organization productivity.